Muros y posterrorismo en Los Gondra y Los otros Gondra de Borja Ortiz de Gondra (Altre Modernità, 2021)
We analyse the representation of the end of ETA’s terrorism in thecontemporary self-fiction theatre. Therefore we study the importance of the physicalwalls considering the symbolical values they represent and the social, mental andemotional barriers that lead the characters to repeat political struggles, generation aftergeneration. The vision of reconciliation and forgiveness may be dark if it becomespossible only when those walls and their cultural background are knocked down, or itcan be bright if it is considered as an emancipation from that background.
Keywords: self-fictional theater; Basque terrorism; trauma writing; forgiveness